Vision-based approach for human motion detection and smart appliance control - Swami, Siddharth; Singh, Rajesh; Gehlot, Anita; Iqbal, Mohammed Ismail; Sharma, Sameer Dev; Kumar, Dharmendra; Shah, Sanjeev Kumar (Institute of Advanced Engineering and Science, 2024)
This study focuses on the use of computer vision technology and motion detection sensors to create an intelligent system that recognizes human presence in monitored spaces. The system uses a relay module for automation and control of household appliances while sensing motion detection, operated by an ESP32 microcontroller. This innovative solution addresses two major issues in home automation: reliable human presence recognition and seamless appliance control. The research merges a camera-based vision system with motion sensors, comparing motion and vision-based identification. The ESP32 microcontroller improves motion detection precision and context awareness by integrating motion sensors and computer vision technologies. The integration of a camera module allows real-time analysis and recognition of human presence, reducing false alarms. The relay module also enables automated control of home appliances, synchronizing and feedbacking operations with sensed human presence. The dynamic adaptation of the system improves user convenience and energy efficiency.